2020
DOI: 10.1027/1614-0001/a000340
|View full text |Cite
|
Sign up to set email alerts
|

Re-conceptualizing Machiavellianism and Social-Cognitive Skills

Abstract: Abstract. Machiavellianism is presumed to encompass advanced social-cognitive skill, but research has generally suggested that Machiavellian individuals are rather deficient in social-cognitive skill. However, previous research on the matter has been limited to measures of (a) Machiavellianism that are unidimensional and saturated with both antagonism and disinhibition and measures (b) only one type of social-cognitive skill. Using a large college sample ( N = 461), we examined how various dimensions of Machia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…The research is also aware of the strengths and weaknesses of diverse Mach scales concerning the factor structure and validity (Dahling et al, 2009;Paulhus & Jones, 2015). Some scholars suggested that different facets of Mach might account for differential or in some cases even opposing effects on empathy (Al Aïn et al, 2013;Hart et al, 2020). Our results support this assumption in that some Mach scales revealed more negative correlations than others did and that some measures even revealed null correlations.…”
Section: Differential Correlations As a Function Of The Theoretical Perspective On Machsupporting
confidence: 80%
See 2 more Smart Citations
“…The research is also aware of the strengths and weaknesses of diverse Mach scales concerning the factor structure and validity (Dahling et al, 2009;Paulhus & Jones, 2015). Some scholars suggested that different facets of Mach might account for differential or in some cases even opposing effects on empathy (Al Aïn et al, 2013;Hart et al, 2020). Our results support this assumption in that some Mach scales revealed more negative correlations than others did and that some measures even revealed null correlations.…”
Section: Differential Correlations As a Function Of The Theoretical Perspective On Machsupporting
confidence: 80%
“…A major point regards the issue that most studies treated Mach as unidimensional, although there is evidence on the superiority of the multidimensional assessment of Mach (e.g., Andreou, 2004;Andrew et al, 2008;Dahling et al, 2009;Hart et al, 2020;Monaghan et al, 2016Monaghan et al, , 2018Monaghan et al, , 2020Sutton & Keogh, 2001). The research is also aware of the strengths and weaknesses of diverse Mach scales concerning the factor structure and validity (Dahling et al, 2009;Paulhus & Jones, 2015).…”
Section: Differential Correlations As a Function Of The Theoretical Perspective On Machmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Mach scales originating from the Mach IV (e.g., TDMS) reveal higher correlations among each other as compared to Mach scales that were developed independently, which applies to the MaaQ (Kavish et al, 2019). Consistent with this, Hart et al (2021) detected predominantly small correlations between the facets of the FFMI (Collison et al, 2018) and those of the TDMS (Monaghan et al, 2020), indicating a general anisomorphy among Mach scales (see also Monteiro et al, 2020). As opposed to both the MaaQ and the TDMS, the SD4-Mach scale does not provide a multidimensional structure.…”
Section: Discussion Study 2 and General Discussionsupporting
confidence: 67%
“…However, Mach scales originating from the Mach IV (e.g., TDMS) reveal higher correlations among each other as compared to Mach scales that were developed independently, which applies to the MaaQ (Kavish et al, 2019). Consistent with this, Hart et al (2020) detected predominantly small correlations between the facets of the FFMI (Collison et al, 2018) and those of the TDMS (Monaghan et al, 2020), indicating a general anisomorphy among Mach scales (see also Monteiro et al, 2020). As opposed to both the MaaQ and the TDMS, the SD4-Mach scale does not provide a multidimensional structure.…”
Section: Discussion Study 2 and General Discussionmentioning
confidence: 59%